Impact of the COVID-19 pandemic on the business environment in Slovakia - Lucia Svabova; Katarina Kramarova; Dominika Chabadova (Economies, 2022)
The COVID-19 pandemic has significantly affected economic development in countries around the world. It has deepened existing problems and increased the need for economic transformation, modernisation, and qualitative development, and launched new technological reforms that have led to the emergence of new economic forms of business models, consumption, as well as policies at the level of the state or local governments. The impacts of the pandemic are still visible in many aspects of life, including economic activity and the individual decisions of economic subjects at the level of households, enterprises, and governments. In this article, we present the results of the impact analysis of the COVID-19 pandemic with an emphasis mainly on the SMEs segment focusing on the tourist, hotel, and gastro industry (generally as one of the most affected by the pandemic). We also analyse the impact of the pandemic on the automotive industry because it is the most important manufacturing industry in Slovakia. Regardless of which industries of the national economy they are operating in, SMEs are assumed to be a driving force of structural changes, increasing employment, and economic growth. SMEs in Slovakia represent approx. 99% of all active enterprises and significantly participate in the success of the national economy. They are also an important factor in cooperation with large enterprises; in the case of Slovakia, the automotive industry should be highlighted (it is an important part of the secondary sector). The analysis and evaluation of the impacts of the COVID-19 pandemic are carried out as a temporal and comparative analysis of the selected economic and industrial indicators relevant to the assessment of the impact of the pandemic on the Slovak business environment. It is an overview study of development; the impact of the pandemic is expressed mostly through the ratio indicators. The basis for time analysis and comparison is data representing the economic status quo before the pandemic (2019), and the ordinary period is represented by data distinctive of the pandemic period (2020, 2021). The results of the analysis indicate that the pandemic had a strong impact on employment and the sales of enterprises operating in the accommodation and catering industries; on the other hand, it did not reflect in the number of defunct enterprises, which points to the potential effectiveness of anti-pandemic measures in terms of state aid for the business sector. The results of this study may serve as a basis for the evaluation of introduced support programs (the evaluation of optimal combination and the impact of fiscal policies during a national/global economic crisis between assisting households, companies, state, and local governments) immediately mitigating the consequences of anti-pandemic measures, but also programs to eliminate the long-term consequences of the pandemic in the business environment in Slovakia. Assessing the situation is also a prerequisite for evaluating the impact of current crises (problems such as the global failure of logistics chains due to the pandemic, inflation, the environmental and energy crisis, and migration due to war conflict and applied sanction measures). In general, it is possible to claim that the pandemic was a huge burden for Slovakia; on the other hand, it was a lesson learned.
Keywords: 330; business environment; COVID-19 pandemic; pandemic impact